Metode dan Strategi Penerjemahan Ungkapan Makian Dalam Novel Imro’ah ‘Inda Nuqṭah Aṣ Ṣifr 'Inda Nuqṭah Aṣ Ṣifr - Ash Shidiqiyah, Firstiyana Romadlon; Mubarokah, Nida Farhani (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2025)
This study aims to identify the form and reference of swear words in Arabic in the novel Imro'ah 'Inda Nuqṭah Aṣ Ṣifr by Nawal As-Sa'dawi. Each language has different cultural characteristics, so when carrying out translation practices a translator must understand the culture of the source text and target text. As for the practice of translating Arabic swear words into Indonesian, a translator needs to understand Arabic and Indonesian cultures to produce an equivalent translation. This study will apply Newmark's V diagram to identify the translation method used by the translator, whether it is oriented towards the source text or the target text. Then continued with the application of Mona Baker's translation strategy. This study is a qualitative descriptive study using the listening and recording method in collecting data. After the research data is collected, the researcher will carry out 3 stages of data analysis, namely reducting data according to classification, presenting data using sampling techniques, and finally drawing conclusions from the data found. The results of the study show that in the novel Imro'ah Inda Nutqah Sifr uses swear words in the form of words, phrases, clauses and sentences. The translation method in the INS novel uses several translation methods, namely: Word-for-word translation, literal translation, faithful translation, semantic translation, adaptation translation, and idiomatic translation. Then the translation strategy uses more translation strategies of reordering.